Profits, Markups and Entry: Fiscal Policy in an Open Economy - Javier Coto-Martínez; Huw D. Dixon (Center for Economic Studies and ifo Institute (CESifo), 2001)
In this paper we develop a general model of an imperfectly competitive small open economy. There is a traded and non-traded sector, whose outputs are combined in order to produce a single final good that can be either consumed or invested. We make general assumptions about preferences and technology, and analyze the impact of fiscal policy on the economy. We find that the fiscal multiplier is between zero and one, and provide sufficient conditions for it to be increasing in the degree of imperfect competition. We also are able to compare the multiplier under free-entry and with a fixed number of firms and welfare. A simple graphical representation of the model is developed.
Keywords: E20; E62; F40; 330; Imperfect competition; open economy; fiscal policy